Life and cancer without telomerase: ALT and other strategies for making sure ends (don't) meet. (2nd January 2017) - Apte, Manasi S.; Cooper, Julia Promisel
Abstract: While most cancer cells rely on telomerase expression/re-activation for linear chromosome maintenance and sustained proliferation, a significant population of cancers (10–15%) employs telomerase-independent strategies, collectively dubbed Alternative Lengthening of Telomeres (ALT). Most ALT cells relax the usual role of telomeres as inhibitors of local homologous recombination while maintaining the ability of telomeres to prohibit local non-homologous end joining reactions. Here we review current concepts surrounding how ALT telomeres achieve this new balance via alterations in chromatin landscape, DNA damage repair processes and handling of telomeric transcription. We also discuss telomerase independent end maintenance strategies utilized by other organisms, including fruitflies and yeasts, to draw parallels and contrasts and highlight additional modes, beyond ALT, that may be available to telomerase-minus cancers. We conclude by commenting on promises and challenges in the development of effective anti-ALT cancer therapies.